Overexpression of CX3CR1 in Adipose-Derived Stem Cells Promotes Cell Migration and Functional Recovery After Experimental Intracerebral Hemorrhage - Li, Gaigai; Yu, Haihan; Liu, Na; Zhang, Ping; Tang, Yingxin; Hu, Yang; Zhang, Ye; Pan, Chao; Deng, Hong; Wang, Jiahui; Li, Qi; Tang, Zhouping (Frontiers in Neuroscience, 2019)
Stem cell therapy has emerged as a new promising therapeutic strategy for intracerebral hemorrhage (ICH). However, the efficiency of stem cell therapy is partially limited by low retention and engraftment of the delivered cells. Therefore, it’s necessary to improve the migration ability of stem cells to the injured area in order to save the costs and duration of cell preparation. This study aimed to investigate whether overexpression of CX3CR1, the specific receptor of chemokine fractalkine (FKN), in adipose-derived stem cells (ADSCs) can stimulate the cell migration to the injured area in the brain, improve functional recovery and protect against cell death following experimental ICH. ADSCs were isolated from subcutaneous adipose tissues of rats. ICH was induced by means of an injection of collagenase type VII. ELISA showed that the expression levels of fractalkine/FKN were increased at early time points, with a peak at day 3 after ICH. And it was found that different passages of ADSCs could express the chemokine receptor CX3CR1. Besides, the chemotactic movements of ADSCs towards fractalkine have been verified by transwell migration assay. ADSCs overexpressing CX3CR1 were established through lentivirus transfection. We found that after overexpression of CX3CR1 receptor, the migration ability of ADSCs was increased both in vitro and in vivo. In addition, reduced cell death and improved sensory and motor functions were seen in the mice ICH model. Thus, ADSCs overexpression CX3CR1 might be taken as a promising therapeutic strategy for the treatment of ICH.